Protection of working women in Peru - Coloma Cieza, Evelin (2022)
Although in recent years there has been a worldwide increase in the legislative regulation on the protection of working women, in our country those are still insufficient to improve quantitatively and qualitatively women’s labor rights, since some of the most flagrant forms of labor discrimination and violence may have decreased, however many remain, and others have transformed or have become less visible. In view of the foregoing, in this article we review the international standards ratified by our country, as well as national regulations on women’s employment, in order to determine the progress and outstanding issues in this matter.